1999
DOI: 10.1017/s0954579499002400
|View full text |Cite
|
Sign up to set email alerts
|

The role of psychopathology in the parenting of drug-dependent women

Abstract: This paper explores the parenting of drug-dependent women and the contributions of comorbid psychopathology to their parenting. A sample of 32 children whose mothers were dependent on opioid drugs during pregnancy and 37 children whose mothers were not drug users were followed from birth to middle childhood. Multivariate regression analyses were conducted contrasting whether maternal substance abuse or psychopathology was more closely linked to parenting behaviors and continuity in parenting over time. Materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
147
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(155 citation statements)
references
References 11 publications
7
147
1
Order By: Relevance
“…In a 10-year study of low-income children first assessed at birth, concurrent maternal opioid abuse had nonsignificant links to child psychopathology at age 10, whereas maternal psychological symptoms other than substance abuse were linked to various child outcomes (Wakschlag & Hans, 1999). Several other studies have shown that among children of heroin or cocaine abusers, psychopathology tends to be particularly high among those whose parents have coexisting depressive problems (Hans, Bernstein, & Henson, 1999;Weissman et al, 1999).…”
Section: Maternal Drug Abuse and Other Psychopathology: Disentanglingmentioning
confidence: 96%
See 1 more Smart Citation
“…In a 10-year study of low-income children first assessed at birth, concurrent maternal opioid abuse had nonsignificant links to child psychopathology at age 10, whereas maternal psychological symptoms other than substance abuse were linked to various child outcomes (Wakschlag & Hans, 1999). Several other studies have shown that among children of heroin or cocaine abusers, psychopathology tends to be particularly high among those whose parents have coexisting depressive problems (Hans, Bernstein, & Henson, 1999;Weissman et al, 1999).…”
Section: Maternal Drug Abuse and Other Psychopathology: Disentanglingmentioning
confidence: 96%
“…Hans, Bernstein, & Henson, 1999). Estimates of the prevalence of affective or anxiety disorders among individuals with histories of substance abuse range from 32% (Regier et al, 1990;Regier, Rae, Narrow, Kaelber, & Schatzeberg, 1998) to as high as 90% (Luthar, Cushing, Merikangas, & Rounsaville, 1998;Weissman et al, 1999).…”
Section: Maternal Drug Abuse and Other Psychopathology: Disentanglingmentioning
confidence: 99%
“…For example, maternal-infant interaction and attachment are areas of concern. Observational studies have shown that, in interaction with their infants, women with substance abuse issues show a lack of sensitivity and responsiveness to emotional cues and heightened physical activity, provocation, and intrusiveness (Hans, Bernstein, & Henson, 1999;Rodning, Beckwith, & Howard, 1991). Research on infants of methodone-using mothers has shown that they demonstrate higher levels of disorganized attachment than infants of nondrug-using mothers (Goodman, Hans, & Cox, 1999;Rodning et al, 1991).…”
Section: Parenting In the Context Of Substance Abusementioning
confidence: 99%
“…These risks include low socio-economic status and limited social support [14,16], comorbid mental disorder and functioning of the mother [1,13,16,20], physical abuse [1,13,16,20], and residential placement or foster care [10].…”
Section: Introductionmentioning
confidence: 99%